2015
DOI: 10.1055/s-0034-1396884
|View full text |Cite
|
Sign up to set email alerts
|

A Non-inferiority Pilot Study Comparing the Clinical Efficacy and Safety of Generic Wide-spectrum Antibiotic Use in Septic Oncology Patients

Abstract: The present study is a non-inferiority study based on a descriptive and comparative case series for comparison of generic vs. original intravenous antimicrobials in septic oncology patients at an oncology private ICU. 1906 cancer patients admitted to Arturo Lopez Perez Foundation, Chile, were included in this study. After recruitment, a first retrospective group of 206 septic cancer patients recorded from 1st January, 2008 until July 14th, 2010, treated with original antibiotics (cefoperazone-sulbactam, imipen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…performed a non‐inferiority study of generic wide‐spectrum antibiotic agents at a septic oncology intensive care unit in Chile. No significant differences between the two groups in days of treatment, rates of treatment success, and laboratory indicators (e.g., white cell counts) were found . Our results, derived from a nationally representative sample and a PS‐matched subject set, were consistent with the previous findings and indicated similar treatment effects of generic antibiotics to their brand‐name counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…performed a non‐inferiority study of generic wide‐spectrum antibiotic agents at a septic oncology intensive care unit in Chile. No significant differences between the two groups in days of treatment, rates of treatment success, and laboratory indicators (e.g., white cell counts) were found . Our results, derived from a nationally representative sample and a PS‐matched subject set, were consistent with the previous findings and indicated similar treatment effects of generic antibiotics to their brand‐name counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…Seven studies showed no statistically significant difference in primary outcomes comparing generic antibiotics and their respective branded counterparts [6,[21][22][23][24]27,28].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…The studies had a heterogeneous population. Araya et al, (2015) [22] analyzed cancer patients, and Punpanich et al, (2012) [23] was the only that included patients under 18 years. Snyman et al, (2009) [6] and Lin et al, (2016) [24] included outpatients, while the others only included inpatients.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Some of these patterns exhibited statistically significant differences, and this approach could have altered the conclusions to some extent, despite the fact that the outcomes in the multivariate analyses were adjusted. The differences can be explained by possible physician fear regarding use of the generic antibiotic in complicated infections, although in clinical and in vitro studies, it has not been demonstrated that the results are different in terms of the resolution of morbidity or mortality (Agudelo et al, 2015;Charoenpong et al, 2013;Araya et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Through in vitro studies, murine models, and observational investigations, it has been shown that the generic form of piperacillin-tazobactam is bioequivalent to the innovator molecules, with no significant difference in pharmacokinetic, effectiveness, or safety parameters (Agudelo et al, 2015;Tschudin-Sutter et al, 2011;Charoenpong et al, 2013;Araya et al, 2015). However, the quality of the generic presentations has been questioned, with some studies reporting that they present lower in vitro activity (Jones et al, 2008;Jones et al, 2013).…”
Section: Introductionmentioning
confidence: 99%